Polyphenolic-Rich Compounds From Dillenia pentagyna (Roxb.) Attenuates the Doxorubicin-Induced Cardiotoxicity: A High-Frequency Ultrasonography Assisted Approach - Tene, Kalyani; Kalyan Kumar, M.; Basveshwar, G.; Eswara Rao, P.; Jagadeesh Kumar, G.; kumar, Pramod; Pemmaraju, Deepak B.; Murty, U. S. N.; Gogoi, Ranadeep; Naidu, V. G. M. (Frontiers in Pharmacology, 2021)
Cardiovascular complications are the foremost concern in patients undergoing anticancer therapy. There is an unmet need to address the problems arising from the drug-induced toxicity for the long-term benefit of the patients undergoing chemotherapy. Alternative medicines are gaining their prosperity in addressing the various drug-induced organ toxicity. Dillenia pentagyna Roxb. (DP) is an ethnomedicinal plant rich in flavonoids and phenolic contents. In India & Nepal, DP is a common ingredient of traditional medicines used to treat multiple ailments like inflammation, cancer, and diabetes. However, its protective role against doxorubicin (Dox) induced cardiotoxicity remains unexplored. Herein,we investigated the potential effects of various extracts/fractions obtained from the DP's bark against Dox-induced cardiotoxicity, both in-vitro & in-vivo. The anti-oxidant content of the extracts/fractions was evaluated by using DPPH, ABTS & FRAP chemical assays. The results indicated that the hydroalcoholic (HA) extract of DP has intense anti-oxidant potential. Further fractionation of DP revealed that the phenolic-rich fraction (F1) has a high anti-oxidant potential. The protective effect of extract/fraction was also investigated in the H9c2 cell line following the Dox-induced cardiotoxicity model. We observed that the pre-treatment of extract/fraction in cardiomyocytes had exhibited increased cell viability. Fluorescence-based chemical assays indicated a decreased ROS levels in the treated groups in comparison to the Dox control group. The effect of DP was evaluated further in balb/c mice by the Dox-induced cardiotoxicity model. Non-invasive techniques like high-frequency ultrasonography and electrocardiogram revealed that the mice pre-treated with DP had improved cardiac functionality (left ventricular ejection fraction and stroke volume) and normalized the electrocardiograms compared to the Dox control group. Further, biochemical analysis with the cardiac tissues revealed that the cytoprotective proteins like HO-1, SOD-2, and Nrf-2 were elevated in the DP treated groups compared to the Dox control group. Overall, our results suggested that the bioactive extract/fractions of DP helped alleviate the Dox-induced cardiotoxicity. LC-QTOF-ESI-MS analysis of DP and F1 indicated that polyphenolic anti-oxidant compounds like gallic acid, syringic acid, and sinapic acid could be responsible for the potent -cardioprotective effect. Future understanding of the pharmacokinetics and pharmacodynamic parameters can help translate from the bench to the bedside.